Black phosphorus-based 2D materials for bone therapy - Cheng, Liang (Bioact Mater, 2020)
Since their discovery, Black Phosphorus (BP)-based nanomaterials have received extensive attentions in the fields of electromechanics, optics and biomedicine, due to their remarkable properties and excellent biocompatibility. The most essential feature of BP is that it is composed of a single phosphorus element, which has a high degree of homology with the inorganic components of natural bone, therefore it has a full advantage in the treatment of bone defects. This review will first introduce the source, physicochemical properties, and degradation products of BP, then introduce the remodeling process of bone, and comprehensively summarize the progress of BP-based materials for bone therapy in the form of hydrogels, polymer membranes, microspheres, and three-dimensional (3D) printed scaffolds. Finally, we discuss the challenges and prospects of BP-based implant materials in bone immune regulation and outlook the future clinical application.